2020
DOI: 10.1186/s13148-020-00904-7
|View full text |Cite
|
Sign up to set email alerts
|

Fecal DNA methylation markers for detecting stages of colorectal cancer and its precursors: a systematic review

Abstract: Background: DNA methylation biomarkers in stool may have applications in early colorectal cancer (CRC) detection; however, their association with stages of CRC carcinogenesis or their performance in detecting various stages is unclear. We aimed to systematically review the evidence for DNA methylation markers in stool for risk stratification or detection of specific CRC stages, as well as precursors of CRC. Methods: We conducted a systematic search in line with the Preferred Reporting Items for Systematic Revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 76 publications
0
14
0
Order By: Relevance
“…20 Usually, the tested results of multitarget assays are measured by the risk scores of regression models, also called probability (ie, a positive sample has a higher probability and a negative sample has a lower probability). 50,51 Therefore, the probability cutoff would be the critical parameter of a test because different cutoff values would result in ambiguous measurements for samples near the threshold. Herein, the algorithm of iColocomf was used to determine a positive measurement as either of the dual targets showed a C T value of <38 in a valid test.…”
Section: Discussionmentioning
confidence: 99%
“…20 Usually, the tested results of multitarget assays are measured by the risk scores of regression models, also called probability (ie, a positive sample has a higher probability and a negative sample has a lower probability). 50,51 Therefore, the probability cutoff would be the critical parameter of a test because different cutoff values would result in ambiguous measurements for samples near the threshold. Herein, the algorithm of iColocomf was used to determine a positive measurement as either of the dual targets showed a C T value of <38 in a valid test.…”
Section: Discussionmentioning
confidence: 99%
“…For example, by conducting a series of genome-wide DNA methylation assays among 20 normal and pre-CRC samples, including 18 low-grade adenomas and 22 high-grade adenomas, Fan et al found that the methylation alterations detected in low-grade adenoma were maintained or increased in high-grade adenoma and cancer ( 25 ). Several studies on DNA methylation biomarkers tested in fecal ( 26 , 27 ) and blood ( 28 , 29 ) samples indicated the potential of epigenetic biomarkers for early CRC diagnosis. The present study showed that DLX6-AS1 hypermethylation was detectable since the NAA stage during colorectal neoplastic progression, suggesting that this epigenetic change is a candidate driver of tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, either quantitative FITs or stool DNA methylation tests may be successfully used to rule in CRC in patients with positive quantitative FIT (f‐Hb > 10 μg/g). Considering the fact that the quality of currently available studies on the accuracy of stool DNA methylation tests is low [86], their clinical utility is still limited. Therefore, further improvement of the accuracy of stool DNA methylation tests and further longitudinal studies conducted in a screening setting are warranted.…”
Section: Discussionmentioning
confidence: 99%